Parent-Teacher Collaboration in Children's Education (Eurasian Journal of Learning and Academic Teaching, 2023)
This article talks about how important the cooperation of parents and educators is in raising a child. Also, several literatures on this topic are analyzed. Taking into account that child education is very important in today's era of globalization, several suggestions are made in this matter. After all, educating the young generation as a well-rounded person is the most important and responsible task for every pedagogue, including parents.